2016
DOI: 10.1007/978-3-319-32034-2_44
|View full text |Cite
|
Sign up to set email alerts
|

Model Selection for Financial Distress Prediction by Aggregating TOPSIS and PROMETHEE Rankings

Abstract: Abstract. Many models have been explored for financial distress prediction, but no consistent conclusions have been drawn on which method shows the best behavior when different performance evaluation measures are employed. Accordingly, this paper proposes the integration of the ranking scores given by two popular multiple-criteria decisionmaking tools as an important step to help decision makers in selecting the model(s) properly. Selection of the most appropriate prediction method is here shaped as a multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The optimization of the properties of these materials can provide important information for the improvement of their mechanical properties for further applications. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is an appropriate method that has been widely applied for the optimization and prediction of various characteristics [49][50][51][52][53][54]. Some investigations on the nanocomposites of iron oxide nanoparticles with polymers have shown that these materials would be appropriate for the function improvement of electrical devices [55][56].…”
Section: Resultsmentioning
confidence: 99%
“…The optimization of the properties of these materials can provide important information for the improvement of their mechanical properties for further applications. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is an appropriate method that has been widely applied for the optimization and prediction of various characteristics [49][50][51][52][53][54]. Some investigations on the nanocomposites of iron oxide nanoparticles with polymers have shown that these materials would be appropriate for the function improvement of electrical devices [55][56].…”
Section: Resultsmentioning
confidence: 99%